2012
DOI: 10.1182/blood-2011-09-377754
|View full text |Cite
|
Sign up to set email alerts
|

The macrophage mannose receptor promotes uptake of ADAMTS13 by dendritic cells

Abstract: ADAMTS13 is a plasma metalloproteinase that regulates platelet adhesion and aggregation by cleaving ultra-large VWF multimers on the surfaces of endothelial cells. Autoantibodies directed against ADAMTS13 prohibit the processing of VWF multimers, initiating a rare and lifethreatening disorder called acquired thrombotic thrombocytopenic purpura. The formation of autoantibodies depends on the activation of CD4 ؉ T cells. This process requires immune recognition, endocytosis, and subsequent processing of ADAMTS13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 41 publications
1
41
0
2
Order By: Relevance
“…30 We previously showed that the MMR, a mannan-sensitive CLR, mediates internalization of ADAMTS13 by DCs. 16 Although mannan significantly reduced ADAMTS13 uptake by macrophages, ADAMTS13 endocytosis seems to be only partly dependent on this C-type lectin, because its uptake by macrophages is not influenced by the presence of the blocking anti-MR antibody clone 15.2 or by the addition of D-mannose or GlcNAc, which interfere with binding of ligands to mannan-sensitive CLRs. 43 These data suggest that MMR does not play a major role in ADAMTS13 internalization by macrophages.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…30 We previously showed that the MMR, a mannan-sensitive CLR, mediates internalization of ADAMTS13 by DCs. 16 Although mannan significantly reduced ADAMTS13 uptake by macrophages, ADAMTS13 endocytosis seems to be only partly dependent on this C-type lectin, because its uptake by macrophages is not influenced by the presence of the blocking anti-MR antibody clone 15.2 or by the addition of D-mannose or GlcNAc, which interfere with binding of ligands to mannan-sensitive CLRs. 43 These data suggest that MMR does not play a major role in ADAMTS13 internalization by macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that the MMR mediates the uptake of ADAMTS13 by DCs. 16 MMR is predominantly internalized into early endosomes 16 and, after release of its ligand, recycles to the plasma membrane. 31 Confocal microscopy revealed that part of the endocytosed ADAMTS13-AF488 co-localized with the MMR (Figure 2C), suggesting that ADAMTS13 and MMR localize to the same endocytic compartment.…”
Section: Adamts13 Uptake By Macrophages Proceeds Via a Mannose Receptmentioning
confidence: 99%
See 3 more Smart Citations